Health Care Practices of Jaffarabadi Buffalo Farmers in Rural Areas of Junagadh District of Gujarat, India (Indian Journal of Animal Production and Management, 2024)
A field study was conducted in Junagadh  district of Gujarat to ascertain the health care  practices followed by Jaffarabadi buffalo owners  and data were collected from randomly selected  320 respondents through personal interview with  the help of structured interview schedule. The  present study revealed that about 63.12 and 17.50  percent of the respondents regularly vaccinated  their buffaloes against Foot and Mouth Disease and  Haemorrhagic Septicaemia disease, respectively.  None of the respondents vaccinated and tested  their buffaloes against brucellosis. Only 18.13  percent of the respondents practiced deworming to  their buffaloes at regular interval and followed  various practices (spraying, dusting and injectable drugs) for control of ecto–parasites (81.56%) and  cleaned animal sheds (76.57%). Only 22.82  percent of the respondents informed that they  treated their sick buffaloes by veterinarian. All the  respondents washed hind quarters of buffalo after  drop of placenta. Most (83.75%) of the respondents  kept diseased animals together with healthy ones  and majority (70.94%) of the respondents removed  the dung twice in a day from animal sheds.
Keywords: health care practices; Jaffarabadi buffalo; Junagadh; Gujarat